MODIFIKASI SISTEM STEERING PADA RANCANG BANGUN KENDARAAN OFFROAD TOYOTA FJ40 - Chandra Anugrah Firdaus, - (2018)
Background to the problem on the steering system of Toyota FJ40 steering load is very heavy and it is not agile. Final project aims to modify the steering system on Toyota FJ40 and knowing how large the force occurred in the manual steering system power steering units and Toyota FJ40. Modifying replacement parts gear box mounting steering and vane pump, to get past some of the calculations but the data calculation pase should know in advance that is the weight of heavy vehicles, the front part of the vehicle, the weight the rear part of the vehicle, wheelbase, 72-82 pump pressure kg/cm2 which is assumed to be from the book of Toyota Astra Motor. The result of the calculations is obtained as follows, a style that works for membelokan the front wheel to the right or to the left when the vehicle is stationary of 285 kg, the load turn the front wheels are affected, the length of the knuckle arm, pitman, the diameter of the steering wheel, the gear comparisons Steering, power piston pressure so that the burden of steering of the front wheels to the steering wheel is worth 5.4 kg for manual steering system and 2.7 kg for the power steering, so the power steering system can be summed up using fewer styles than the manual steering.